One-pot synthesis of bimodal (macro-meso, micro-mesoporous) silica by polyHIPE: parameter studies - Wale, Apparav; Nalawade, Archana; Ponrathnam, Surendra; Rajan, C. R.; Badiger, Manohar (Journal of Porous Materials, 2020)
Porous silica with hierarchical organization of pore structure is desired for a variety of applications such as, chromatography, sensing, control release, scaffold for biomedical applications and catalysis. Highly porous polymers obtained from high internal phase emulsion (HIPE) templating route have attracted increasing attention of researchers due to their hierarchical porous and interconnected structure with high porosity and low density. The novel method adopted in our approach combines redox initiated polymerization using HIPE polymerization and an in-situ sol-gel processing technique followed by calcination to obtain highly porous materials. The obtained materials have reminiscent of polyHIPE morphology containing pores and interconnected pore throats in micrometer size range with mesopores on the wall of macropores. The effect of concentration of TEOS, volume of dispersed phase, crosslinker concentration, shear rate and surfactant concentration as well as variation in calcination temperatures on the properties of silica materials were examined.
Keywords: Mesoporous material; PolyHIPE; Polymer-silica hybrid; Porous silica